MANAJEMEN PENGELOLAAN HUTAN KOTA VELODROME GUNA MENINGKATKAN FUNGSI RUANG TERBUKA HIJAU - Bete, Cornelio Rosalino Mau; Djoko, Riyanto; Alvian, Rizki (Universitas Tribhuwana Tunggadewi, 2019)
Urban Forests are areas covered by trees that are allowed to grow naturally which resemble forests that are not arranged like a park, and their location is in or around the city. This research took place in the Velodrome City Forest at Jln. Simpang Terusan Danau Sentani, Kecamatan, Kedung Kandang Malang City The data obtained will be analyzed using qualitative descriptive method, to find out the existing conditions in the form of physical, biophysical social with the City Forest management system related to the Planing Organizing, Actuating and Controling (POAC) aspects. Based on the results of the research conducted, it can be concluded in the Velodrome Urban Forest that several problems were identified, including the Housing and Settlement Area as a Velodrome City Forest Management not yet having a master plan, and the Velodrome Urban Forest management organization has not run properly according to its function and role, Housing Agency And the Poor Settlement Area has a special maintenance budget plan. From these problems there are several recommendations for several aspects, 1) Planning Aspects (Planing). there needs to be a Master Plan for planning the management of Velodrome Urban Forest and establishing a velodrome urban forest maintenance budget plan itself. 2) Organizing Aspects need to be redesigned in the organizational structure for Velodrome Urban Forest so that the organization is organized and organized. 3) Actuating aspects need an organization that regulates all Velodrome Urban Forest management activities. 4) Controlling activities, is the most important thing in an activity, it is necessary to add field officers to control all activities in the field so that all activities in the Velodrome Urban Forest can run smoothly. Hutan Kota adalah kawasan yang ditutupi pepohonan yang dibiarkan tumbuh secara alami yang menyerupai hutan tidak tertata seperti taman, dan lokasinya berada di dalam atau di sekitar perkotaan. Penelitian ini bertempat di Hutan Kota Velodrome di Jln. Simpang Terusan Danau Sentani, Kecamatan, Kedung Kandang Kota Malang Data yang didapat akan dianalisis menggunakan metode diskriptif kualitatif, untuk memgetahui kondisi eksisting yang berupa fisik, biofisik sosial dengan sistem pengelolaan Hutan Kota terkait aspek Planing Organizing, Actuating dan Controling (POAC). Berdasarkan hasil penelitian yang dilakukan dapat disimpulkan di Hutan Kota Velodrome terdapat beberapa permasalahan yang teridentifikasi diantaranya, Dinas Perumahan Dan Kawasan Permukiman sebagai pengelolah Hutan Kota Velodrome belum memiliki master plan, dan organisasi pengelolaan Hutan Kota Velodrome belum berjalan dengan baik sesuai fungsi dan perannya, Dinas Perumahan Dan Kawasan Permukiman belun mempunyai rencana anggaran pemeliharaan yang khusus. Dari permasalahan-permasalahan tersebut terdapat beberapa rekomendasi untuk beberapa aspek, 1) Aspek Perencanaan (Planing). perlu adanya Master Plan untuk perencnaan pengelolan Hutan Kota Velodrome dan menetapkan rencana anggaran pemeliharaan hutan kota velodrome itu sendiri 2) Aspek Organisasi (Organizing) perlu dirancang ulang struktur pengorganisasian untuk Hutan Kota Velodrome agar organisasinya terarah dan teratur. 3) aspek pelaksanaan (Actuating) perlu adanya organisasi yang mengatur seluruh kegiatan pengelolaan Hutan Kota Velodrome. 4) Kegiatan pengawasan (Controling), merupakan hal terpenting dalam suatu kegiatan, maka perlu ditambahkan petugas lapangan untuk mengotrol seluruh kegiatan dilapangan agar semua kegiatan di Hutan Kota Velodrome dapat berjalan dengan lancar.